(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Polycystic ovary syndrome (PCOS) is one of the common disorder in female. Polycystic ovary syndrome causes irregular menstrual cycles, excessive body or facial hair and polycystic ovaries as its main symptoms. Polycystic means "many cysts," and PCOS often causes clusters of small, pearl-sized cysts in the ovaries. The cysts are fluid-filled and contain immature eggs. Women with PCOS produce higher amounts of androgens a male hormones, which leads to some of the symptoms of PCOS. PCOS is an emerging lot of health problem during adolescence therefore promotion of healthy lifestyles and early interventions are required to prevent future morbidities. Stress is one of the factor that deeply rooted in the society and women are most frequently exposed to psychological, physical and physiological stressors. PCOS cannot be prevented, but early diagnosis and treatment helps to prevent long-term complications, such as infertility, diabetes , obesity, metabolic syndrome and some heart disease. In India , prevalence rate of PCOS is higher and most of the cases reported in Maharashtra (22% upto year 2020) as compared to other state of India.Main body:Shatavari and Shatpushpi both are used as tonic for female reproductive system. Effectiveness of combination of Shatavari and Shatpushi is utilize in treatment of PCOS.Overactive pituitary gland start to secreat high amount of luitenizing hormone in bloodstream which disrupt normal menstrual cycle due to which follicle does not mature and ovulation does not takes place. As because of irregular ovulation hormonal imbalance occur and that leads to increase secrestion of testosterone. High level of testosterone leads to infertilityConclusion: This review describe that easily available beneficial herbs, Shatavari and Shatpushi along with lifestyle management is much effective in prevention of PCOS than allopathic treatment which have large side effects.